Development of an EAT-Lancet index and its relation to mortality in a Swedish population. Issue 3 (13th November 2021) - Stubbendorff, Anna; Sonestedt, Emily; Ramne, Stina; Drake, Isabel; Hallström, Elinor; Ericson, Ulrika
ABSTRACT: Background: Current global food systems threaten human health and environmental sustainability. In 2019, the EAT-Lancet Commission on healthy diets from sustainable food systems defined the first global reference diet to improve both areas, but there is no consensus on how to quantify the EAT-Lancet reference diet as a diet index, and its relation to mortality has not been widely studied. Objectives: We sought to develop a new dietary index to quantify adherence to the EAT-Lancet diet and assess its association with mortality in a large, population-based Swedish cohort. We also examined food components included in the index and their individual associations with mortality. Methods: We used the Malmö Diet and Cancer cohort ( n  = 22, 421; 45–73 years old at baseline). Dietary data were collected using a modified diet history method. The EAT-Lancet index was developed based on intake levels and reference intervals of 14 food components defined in the EAT-Lancet diet (0–3 points per component; 0–42 points in total). Associations with mortality were examined based on registers during a mean of 20 years of follow-up and were adjusted for potential confounders. Results: Divided into 5 adherence groups, the highest adherence to the EAT-Lancet diet (≥23 points) was associated with lower all-cause mortality (HR, 0.75; 95% CI, 0.67–0.85), cancer mortality (HR, 0.76; 95% CI, 0.63–0.92), and cardiovascular mortality (HR, 0.68; 95% CI, 0.54–0.84) than the lowest adherence (≤13 points). Several food components included in the index contributed to the observed reductions in mortality. Conclusions: We developed a new dietary index to investigate adherence to the EAT-Lancet diet. The findings indicate a 25% lower risk of mortality among those with the highest adherence to the EAT-Lancet diet, as defined using our index, which adds to the evidence base for the development of sustainable dietary guidelines.